2004
DOI: 10.1086/424698
|View full text |Cite
|
Sign up to set email alerts
|

NIPBL Mutational Analysis in 120 Individuals with Cornelia de Lange Syndrome and Evaluation of Genotype-Phenotype Correlations

Abstract: The Cornelia de Lange syndrome (CdLS) is a multisystem developmental disorder characterized by facial dysmorphia, upper-extremity malformations, hirsutism, cardiac defects, growth and cognitive retardation, and gastrointestinal abnormalities. Both missense and protein-truncating mutations in NIPBL, the human homolog of the Drosophila melanogaster Nipped-B gene, have recently been reported to cause CdLS. The function of NIPBL in mammals is unknown. The Drosophila Nipped-B protein facilitates long-range enhancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
334
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(354 citation statements)
references
References 33 publications
16
334
1
3
Order By: Relevance
“…A deletion removing the NIPBL region, however, was seen in a severe case of CdLS, supporting the idea that loss-offunction mutations cause CdLS (Hulinsky et al 2003). Many of the less severe cases of CdLS are associated with mutations that cause amino acid substitutions, although the general correlation of milder CdLS cases with missense mutations and more severe forms with truncations has exceptions (Bhuiyan et al 2005;Gillis et al 2004). Many polymorphisms are found in unaffected parents, and in addition to numerous other genetic differences between individuals, these polymorphisms could contribute to the phenotypic variability of the syndrome.…”
Section: Cornelia De Lange Syndrome (Cdls)mentioning
confidence: 71%
See 1 more Smart Citation
“…A deletion removing the NIPBL region, however, was seen in a severe case of CdLS, supporting the idea that loss-offunction mutations cause CdLS (Hulinsky et al 2003). Many of the less severe cases of CdLS are associated with mutations that cause amino acid substitutions, although the general correlation of milder CdLS cases with missense mutations and more severe forms with truncations has exceptions (Bhuiyan et al 2005;Gillis et al 2004). Many polymorphisms are found in unaffected parents, and in addition to numerous other genetic differences between individuals, these polymorphisms could contribute to the phenotypic variability of the syndrome.…”
Section: Cornelia De Lange Syndrome (Cdls)mentioning
confidence: 71%
“…The first CdLS gene was mapped by linkage exclusion analysis and a de novo balanced translocation affecting the 5p13.1 region, which is one of the five non-excluded regions Tonkin et al 2004). Subsequent analysis revealed mutations in the NIPBL gene in 5p13.1 in many of the patients, and now several studies have identified a variety of NIPBL mutations in CdLS patients (Borck et al 2004;Bhuiyan et al 2005;Gillis et al 2004;Krantz et al 2004;Miyake et al 2005;Tonkin et al 2004). …”
Section: Cornelia De Lange Syndrome (Cdls)mentioning
confidence: 99%
“…Each missense mutation affects a residue conserved in human NIPBL, and all are close to conserved residues altered by CdLScausing missense NIPBL mutations ( Fig. 2; Gillis et al 2004;Miyake et al 2005;Schoumans et al 2007). Two other Nipped-B mutations, Nipped-B NC7 and Nipped-B NC59 , truncate the encoded protein in the C-terminal region after the HEAT repeats, and four, Nipped-B NC6 , Nipped-B NC23 , Nipped-B NC41 , and Nipped-B NC77 , truncate the protein in the N-terminal region before the HEAT repeats.…”
Section: And 4)mentioning
confidence: 97%
“…NIPBL maps to chromosome 5p13.2 and encodes delangin, the mammalian ortholog of Drosophila Nipped-B and yeast Scc2 which are both involved in sister chromatid cohesion by loading cohesin complexes onto chromatin (Strachan, 2005;Dorsett, 2006). CdLS-causing mutations are scattered throughout this large gene and include nonsense, frameshift, splice site, and missense DOI: 10.1002/humu.9478 mutations, as well as a mutation in the 5'untranslated region (5'UTR) and small in-frame deletions (Borck et al, 2004;Gillis et al, 2004;Krantz et al, 2004;Tonkin et al, 2004;Miyake et al, 2005;Bhuiyan et al, 2006;Borck et al, 2006;Yan et al, 2006). Absence of NIPBL mutations in half of affected persons suggested genetic heterogeneity in CdLS.…”
Section: Introductionmentioning
confidence: 99%